1991
DOI: 10.1128/mcb.11.3.1353
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitous transcription factor Oct-1 and the liver-specific factor HNF-1 are both required to activate transcription of a hepatitis B virus promoter.

Abstract: The liver-specific transcription factor HNF-1 activates transcription of several mammalian hepatocytespecific genes. The hepatitis B virus preSl promoter shows hepatocyte specificity, which has been ascribed to binding of HNF-1 to a cognate DNA sequence upstream of the TATA box. We show here that there is an adjacent site that binds the ubiquitous transcription factor Oct-1. Both the Oct-1 and HNF-1 sites are necessary for liver-specific transcription of the preSl promoter, but neither site alone activates tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 54 publications
2
44
0
1
Order By: Relevance
“…The various Pbx proteins were synthesized in vitro and shown to have migrations in SDS gels corresponding to their respective predicted molecular weights: Pbxla, 46,500; Pbxlb, 38,400; Pbx2, 45,900; Pbx3a, 47,100; and Pbx3b, 38,800 (Fig. 6A) domains (26,27) (14) and U4B small nuclear RNA genes (59) and also in DNA replication (45,48,56 (60) have demonstrated that Oct-i and the liver-specific transcription factor HNF1 were both necessary for liver-specific transcription of the hepatitis B virus pre-Sl promoter.…”
Section: Resultsmentioning
confidence: 99%
“…The various Pbx proteins were synthesized in vitro and shown to have migrations in SDS gels corresponding to their respective predicted molecular weights: Pbxla, 46,500; Pbxlb, 38,400; Pbx2, 45,900; Pbx3a, 47,100; and Pbx3b, 38,800 (Fig. 6A) domains (26,27) (14) and U4B small nuclear RNA genes (59) and also in DNA replication (45,48,56 (60) have demonstrated that Oct-i and the liver-specific transcription factor HNF1 were both necessary for liver-specific transcription of the hepatitis B virus pre-Sl promoter.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of synergism, the level of transcription activation produced by two factors is higher than the sum of the effects produced by each of these factors alone (81,84,(128)(129)(130)(131) (85,127,128,(135)(136)(137)(138)(139).…”
Section: Introductionmentioning
confidence: 99%
“…One factor can be tissue-specific, one ubiquitous (66,79,80,85,127,128,129), one inducible, one constitutive (74,93,122,126) or both can be inducible yet activated by different molecular signals (70,133,141,143). The interactions between such elements are exemplified in the compilation, where the functional properties of the complexes are described in the column 'Comments' (see Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…These results show that additional HBV sequences are not necessary for HNFl-mediated transcriptional activation from this promoter. A previous report suggested that both the Oct-1 and HNF 1 transcription factors were essential for HNFl-mediated transcriptional activation from the large surface antigen promoter (Zhou & Yen, 1991). However, the results of the clustered point mutation and synthetic promoter transfection analyses indicate that the Oct-1 binding site located between -61 and -54 is not necessary for HNFl-mediated transcriptional activation.…”
Section: Discussionmentioning
confidence: 83%